2023
DOI: 10.3390/jdb11010006
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Bridge between Aquatic and Terrestrial Life: Skin Changes during Development of Amphibians

Abstract: Amphibian skin is a particularly complex organ that is primarily responsible for respiration, osmoregulation, thermoregulation, defense, water absorption, and communication. The skin, as well as many other organs in the amphibian body, has undergone the most extensive rearrangement in the adaptation from water to land. Structural and physiological features of skin in amphibians are presented within this review. We aim to procure extensive and updated information on the evolutionary history of amphibians and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…In contrast, the open canopies in the plantations decrease humidity and shelter availability (Hardwick et al., 2015). This affects amphibians in particular because their skin is highly permeable (Akat Çömden et al., 2023) and is especially unbearable for forest specialists (Faruk et al., 2013; Foster et al., 2011; Zainudin et al., 2019). Conversely, generalist species, such as the Boie's wart frog ( Fejervarya limnocharis ) and the common greenback ( Hylarana erythraea ), prefer plantations due to the reduced competition and opportunistic spawning grounds (puddles or tracks) left by harvest trucks (Paoletti et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the open canopies in the plantations decrease humidity and shelter availability (Hardwick et al., 2015). This affects amphibians in particular because their skin is highly permeable (Akat Çömden et al., 2023) and is especially unbearable for forest specialists (Faruk et al., 2013; Foster et al., 2011; Zainudin et al., 2019). Conversely, generalist species, such as the Boie's wart frog ( Fejervarya limnocharis ) and the common greenback ( Hylarana erythraea ), prefer plantations due to the reduced competition and opportunistic spawning grounds (puddles or tracks) left by harvest trucks (Paoletti et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These latter have biphasic lifecycles occurring in both aquatic and terrestrial systems, as they are very sensitive to the consequences of environmental threats, way more than other species due to the peculiarities of their skin [17]. This organ is very complex, responsible for respiration, osmoregulation, thermoregulation, and adsorption, and makes the amphibians valid biosentinels [18]. Previews studies reported the efficacy of Hyla cinerea (Garman, 1892), Ambystoma barbourin (Kraus and Petranka, 1989), Rana pipiens (Schreber, 1782), Rana clamitans (Latreille, 1801), Xenopus laevis (Daudin, 1802), Bufotes viridis (Laurenti, 1768) as rapid responders of environmental contamination and ecological damage [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The integument of anurans performs several functions that are necessary for the survival of the species, being constituted by the epidermis and dermis. It participates in gas exchange, osmoregulation, thermoregulation, defense against macropredators and micropredators, and skin lubrication [5]. The integument contains mucous and granular glands, which contribute to protection against predators [6].…”
Section: Introductionmentioning
confidence: 99%